2020
DOI: 10.1634/theoncologist.2020-0502
|View full text |Cite
|
Sign up to set email alerts
|

Tepotinib Efficacy in a Patient with Non-Small Cell Lung Cancer with Brain Metastasis Harboring an HLA-DRB1-MET Gene Fusion

Abstract: Alterations in c‐MET, a tyrosine kinase receptor encoded by the MET gene, have been reported in approximately 3% of non‐small cell lung cancer (NSCLC) cases and carry important treatment implications. The best studied genetic alterations are exon 14 skipping and gene amplification; however, gene rearrangement has also been described, and multiple fusion partners have been reported. Recently, in METex14‐mutated NSCLC, multitarget tyrosine kinase inhibitors (TKIs), such as crizotinib and cabozantinib, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Human leukocyte antigen (HLA), located on chromosome 6, encodes genes that are crucial in the immune response to pathogens (15). There have been 4 described cases of HLA-DRB1-MET gene rearrangement in lung adenocarcinoma (16)(17)(18)(19). Davies et al reported the first case of HLA-DRB1-MET gene rearrangement who was detected a previously undescribed fusion of HLA-DRB1 exon 5 (NM_002124) to MET exon 15 (NM_000245) (18).…”
Section: Discussionmentioning
confidence: 99%
“…Human leukocyte antigen (HLA), located on chromosome 6, encodes genes that are crucial in the immune response to pathogens (15). There have been 4 described cases of HLA-DRB1-MET gene rearrangement in lung adenocarcinoma (16)(17)(18)(19). Davies et al reported the first case of HLA-DRB1-MET gene rearrangement who was detected a previously undescribed fusion of HLA-DRB1 exon 5 (NM_002124) to MET exon 15 (NM_000245) (18).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis showed that c-Met overexpression correlated to distant metastasis, large tumour size and high histologic grade in breast cancer ( Zhao et al, 2017 ). MET gene fusions have been primarily identified in lung cancer such as the HLA-DRB1-MET ( Davies et al, 2017 ; Blanc-Durand et al, 2020 ), KIF5B-MET ( Gow et al, 2018 ), MET-UBE2H ( Zhu et al, 2018a ), and MET-ATXN7L1 ( Zhu et al, 2018b ). The first case of HLA-DRB1-MET fusion was reported, however further studies are required to elucidate the specific mechanisms of the fusion gene ( Davies et al, 2017 ).…”
Section: Receptor Tyrosine Kinase Activationmentioning
confidence: 99%
“…Meanwhile, it was also proposed that the MET-UBE2H fusion protein could be a novel resistance mechanism against EGFR-TKI treatment ( Zhu et al, 2018a ). MET fusions that occur at exon 15 and contain the 3’ MET kinase domain are thought to become activated due to constitutive dimerization of MET ( Blanc-Durand et al, 2020 ).…”
Section: Receptor Tyrosine Kinase Activationmentioning
confidence: 99%
“…The VISION and INSIGHT trials, along with three separately published case reports, have also indicated that tepotinib has intracranial activity. [56][57][58][59][60] These findings prompted FDA accelerated approval for tepotinib for METex14 skipping NSCLC in February 2021. 61 Future studies evaluating genomic or other clinical determinants of response may help better differentiate the two promising drugs.…”
Section: Comparisons To Other Met Targeted Therapiesmentioning
confidence: 99%